Agerbrugets Udvikling i Danmark i de sidste 25 Aar. Foredrag, d. 29de Marts 1871. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Agerbrugets Udvikling i Danmark i de sidste 25 Aar. Foredrag, d. 29de Marts 1871.